Geophysical evidence of first stages of inflation in Domuyo volcanic center in northwestern Neuqu ́en province, Argentina - Godoy, Laura B. (2020)
Fil: Godoy, Laura. CONICET (Consejo Nacional de Investigaciones Científicas y Técnicas). Instituto Geofísico Sismológico F. Volponi, FCEFyN, Universidad Nacional de San Juan (UNSJ). Argentina.